Aristotle the biologist: from the good life to the moral consideration of animals - Goyenechea, Elisa (Las Torres de Lucca. International Journal of Political Philosophy, 2026)
The article is divided into two sections. The first one elaborates on Aristotle´s theoretical approach when investigating the behaviour of sentient beings. In this regard, his reluctance to use universal ideas under which to classify the particular, and his use of analogical metaphor as a recurring strategy to describe the capacities and “character” (Aristoteles, 1995, 488b13) of sentient beings. The second section puts forward the argument that the insurmountable gap between human and non-human animals, as posited in his political works, is not present in his biological texts. We conclude that, based on an examination of the capacities of sentient animals, it is appropriate to distinguish between those who are alive and those who live well, flourish or thrive (Nussbaum, 2022). This distinction forms the basis for the moral consideration of animals and the possibility of making them subjects of rights.
Keywords: Aristotle; Animals; Metaphore; To Live; To Live Well